PROFIL PERESEPAN OBAT BATUK DI RUMAH SAKIT ISLAM JAKARTA PONDOK KOPI PERIODE JANUARI- MARET 2019 - Doni Iswandani; Siti Aisyah; Anne Fajriana Dewi (Jurnal Farmasi IKIFA, 2021)
One of the most common signs of disease or clinic in lung and respiratory diseases. Coughing is one of the ways the body's respiratory tract from mucus or incoming foreign material and objects. Coughing is done as an immune or body protection against objects that can be used also as a symptom of an illness. Stimulants that cause coughing can come from the environment or disease. If the cause is from the environment, then the cough that occurs is a cough in the form of a reflection of the body's defenses, for example choking on food / liquids, cigarette irritation or moving vehicles, cold or hot temperatures. In the preliminary test conducted at Pondok Kopi Islamic Hospital on the prescription profile of cough medicine in December 2018 there were 347 cough medicine prescriptions when further investigated the cough medicine prescribed based on its active substance namely Ambroxol 25.46%, Acetylcysteine ​​13.05%, Erdostein 22.52%, Bromhexin 13.88%, and Guaifenesin 25.09%. The purpose of this study was to determine the profile of cough medicine prescribing at Pondok Kopi Islamic Hospital in the period January - March 2019 based on active substances, dosage forms, and accompanying drugs. The research method used is descriptive quantitative retrospective nature by taking primary data from prescriptions in patients at Pondok Kopi Islamic Hospital. The results of this study show that the most active prescription of guaifenesin is 469 recipes (26.20%). syrup was prescribed as many as 518 sheets (28.43%). The accompanying drug was the most prescribed analgesic-antipyretic group as many as 547 sheets (29.09%). The conclusions from this study that were most prescribed based on active substances, dosage forms, and accompanying drugs were guaifenesin, syrup, and analgesic-antipyretic. While the least prescribed were bromhexin, drop, and vitamins.